MENINGKATKAN KEMAMPUAN MENGENAL BILANGAN MELALUI MEDIA PAPAN FLANEL PADA ANAK USIA 5-6 TAHUN DI TK WAHIDIN KECAMATAN BANGKO KABUPATEN ROKAN HILIR - Rosmawita, Rosmawita; Indarto, Wusono; Risma, Devi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract: The background of this study is that not all children are able to count and recognize numbers are still low capacity, matching numbers and symbols of numbers, such as: the child is able to count the sequence, but when shown the symbol numbers of children are not familiar with, then when asked to match the numbers with the symbol numbers only some children are able to match it. Seeing the conditions that exist in the field that need to be efforts to improve the ability to know the number of children is through the media flannel board. The purpose of this study was to determine whether there is an increased ability to know the number of children through the media and the flannel board to determine how improvements occur. This research is a classroom action research conducted in two cycles. Data collection tool used in this research is observation sheet. The number of samples in this study 20 children rang consisting of 9 boys and 11 girls. Based on the analysis of the assessment process there was an increase of 2 cycles. Improvement occurred, ie from before the action to the first cycle of 40.62%, an increase in cycle I to cycle II is 44.45%, and increased from the prior actions to cycle II of 93.35%. From these results it can be concluded that through the media flannel board can improve the ability to know the number of children aged 5-6 years in kindergarten Wahidin District of Bangko Rokan Hilir.Keywords: Ability Know Numeral, Flannel Board